2015
DOI: 10.7287/peerj.preprints.651v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Does polyandry really pay off?: The effects of multiple mating and number of fathers on morphological traits and survival in clutches of nesting green turtles at Tortuguero

Abstract: View the peer-reviewed version (peerj.com/articles/880), which is the preferred citable publication unless you specifically need to cite this preprint. Despite the long debate of whether or not multiple mating benefits the offspring, studies still show contradicting results. Multiple mating takes time and energy. Thus, if females fertilize their eggs with a single mating, why to mate more than once? We investigated and inferred paternal identity and number of sires in 12 clutches (240 hatchlings) of green turt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 9 publications
1
6
1
Order By: Relevance
“…In summary, our work helps resolve a long-standing conundrum by supporting the suggestion (Alfaro-Núñez et al, 2015;Jensen et al, 2006;Lee and Hays, 2004;Wright et al, 2013) that multiple paternity generally offers no fitness benefits to female sea turtles and simply scales with the density of turtles on the breeding grounds. The use of movement data to estimate male-female encounter rates may allow the broader applicability of this conclusion to be assessed for other taxa.…”
Section: Movement Appears Critical To Estimating Density and Mate Encsupporting
confidence: 56%
See 1 more Smart Citation
“…In summary, our work helps resolve a long-standing conundrum by supporting the suggestion (Alfaro-Núñez et al, 2015;Jensen et al, 2006;Lee and Hays, 2004;Wright et al, 2013) that multiple paternity generally offers no fitness benefits to female sea turtles and simply scales with the density of turtles on the breeding grounds. The use of movement data to estimate male-female encounter rates may allow the broader applicability of this conclusion to be assessed for other taxa.…”
Section: Movement Appears Critical To Estimating Density and Mate Encsupporting
confidence: 56%
“…1). No evidence for genetic (indirect) benefits has so far been detected (Alfaro-Núñez et al, 2015;Lee and Hays, 2004;Wright et al, 2013) with fitness indicators such as clutch size, hatching success or offspring quality being typically compared between single-fathered clutches and those with multiple fathers. However, it has also been argued that indirect benefits may only be easily detected in genetically impoverished and inbred populations (Madsen, 2008).…”
Section: Sea Turtles As a Model Group For Exploring Patterns Of Multimentioning
confidence: 99%
“…Variation in the frequency of multiple paternity has also been demonstrated in studies of the mating system of marine turtle populations including Chelonia mydas (92%: Alfaro-Núñez et al 2015;61%: 75%: Pearse et al 2001;Lee and Hays 2004;9%: FitzSimmons 1998) and Caretta caretta (31%: Moore and Ball 2002;33%: Harry and Briscoe 1988), as well as the freshwater turtle, Chrysemys picta (0%: McTaggart 2000; 13%: Pearse et al 2001;33%: Pearse et al 2002). Some authors suggest that the rate of multiple paternity found in populations different factors, such a scarcity of resources, which is likely to reduce the population density and thus the number of copulations (Engqvist 2011).…”
Section: Discussionmentioning
confidence: 83%
“…The latter should aim to increase the number of males that will potentially fertilize the eggs (Alfaro-Núñez et al 2015), to provide higher rates of multiple paternity and consequently to maintain or increase intrapopulation genetic variability (Sugg andChesser 1994, Chesser andBaker 1996).…”
Section: Discussionmentioning
confidence: 99%
“…However, the application of nuclear DNA markers as an alternate tool has transformed such research, by providing direct insights into parentage in natural populations (Packer et al, 1991;Craighead et al, 1995;Keane, Dittus & Melnick, 1997;FitzSimmons, 1998;Uller & Olsson, 2008) and enabling investigation into the genetic consequences of multiple matings. For example, genetic polyandry of surveyed birds species occurs regularly in 86% of the species (Michl et al, 2002;Griffith, Owens & Thuman, 2002). As a result, sperm from different males may compete to fertilize a single clutch of eggs.…”
Section: Introductionmentioning
confidence: 99%